Prevalence of mental disorders among high school students in National Guard Housing, Riyadh, Saudi Arabia - Abdulrhman M Al-Sughayr; Mazen S Ferwana (Wolters Kluwer Medknow Publications, 2012)
Background: Adolescents experience rapid biological, psychological, and social transitions that can be associated with mental health problems. During the high school period there are also more academic stressors. Objective: (1) To study the prevalence of mental disorders in high school (grade 12) students. (2) To study some related sociodemographic data. Materials and Methods: A cross-sectional study, using GHQ-28, that included 354 students randomly selected from grade 12 in four high schools - two male and two female high schools - in the National Guard Housing (Iskan), in Kashmalaan (suburb of Riyadh). Results: The overall prevalence of mental disorders was found to be 48% (41% in males and 51% in females); more than 80% of these cases were mild to moderate. Females showed significantly more severe disorders than males (P = 0.017) and students with excellent performance degrees showed a significantly lower rate of mental disorders than others (P = 0.021). However, our study did not show a significant association between psychiatric disorders and other social variables (family size, birth order, and polygamous family) or smoking. Conclusion: The adolescent age groups in our community had high rates of mental disorders, which required more attention from the family, as well as the educational and health institutes in our country.